Cesarean delivery rates for overall and multiple pregnancies in Japan: A descriptive study using nationwide health insurance claims data. Issue 6 (28th March 2021) - Maeda, Eri; Ishihara, Osamu; Tomio, Jun; Miura, Hiroshi; Kobayashi, Yasuki; Terada, Yukihiro; Murata, Katsuyuki; Nomura, Kyoko
Abstract: Aim: Due to the lack of national perinatal registries, population‐wide descriptive statistics on cesarean deliveries in Japan are unknown. We aim to describe cesarean deliveries for overall and multiple pregnancies using the Japan National Database of health insurance claims. Methods: We calculated the national and prefectural cesarean delivery rates for overall and multiple pregnancies in 2014. We described maternal morbidities (e.g., blood transfusion) and the place and type of the institutions providing prenatal and perinatal care. Results: The national cesarean delivery rates were 18.6% overall and 82.7% for women with multiple pregnancies. Prefectural cesarean delivery rates for overall and multiple pregnancies varied from 12.5% to 24.2% and from 49.2% to 100%, respectively, showing a moderate positive correlation ( r = 0.59, p < 0.001). Overall, 1.4% of cesarean patients received an allogeneic blood transfusion, compared to 3.2% for those with multiple pregnancies. In addition, 65.9% of overall cesarean deliveries occurred at hospitals with ≥20 beds, whereas 94.6% of cesarean patients with multiple pregnancies delivered at hospitals. Older patients were more likely to receive their cesarean section at a different institution than their first visit within the same prefecture, but trans‐prefectural movement during pregnancy covered by health insurance was most frequent among those in their early thirties: 7.0% overall and 10.7% for multiple pregnancies. Conclusions: The overall cesarean delivery rate in Japan was optimal, but the rate was high for multiple pregnancies, with large regional differences. Data on patient movement across institutions and areas would help to improve the perinatal care system.